Speciation of Heavy Metals in Bottom Sediments of Karra River, Nepal - Pradhanang, Sadhana (Tribhuvan University Journal, 2013)
The chemical forms of copper and zinc have been determined using the fractional scheme of Tessier et al. (1979) in the bed sediments of Karra River, Hetauda, Nepal. The sequential extraction revealed that high percentage of metals was associated in the residual fraction (upstream and downstream). However, in most of the sites in the industrial belt, a significant proportion of metal was associated with the non-residual fraction (64% in Cu and 45% in Zn) which can be remobilized and released to the environment by various physical-chemical processes. This indicates influence of anthropogenic activities on the Karra River